STUDENTS’ RESPONSES ON THE EFFECTIVENESS OF THE ODD AND EVEN NUMBER SYSTEMS DURING COVID-19 OUTBREAK - Khidir, Karnida; Riza, Armilia; Elmiati, Elmiati (Jurnal Pendidikan Nasional, 2022)
This research was motivated by changes in the learning system carried out due to the covid-19 pandemic. This study relates to the effectiveness of learning using the odd-even system that is felt by teachers and students. This study aims to determine whether the teaching and learning of the odd-even system is effective for teachers and students at SMP Negeri 1 Luhak Nan Duo. This type of research is a qualitative description. The participants of this research are teachers who teach in class VIII and students in class VIII at SMP Negeri 1 Luhak Nan Duo. This study uses a total sampling of 2 teachers who teach in class VIII and 230 students in class VIII. The instruments used in this study were questionnaires and interviews. In this study, researchers collected data by distributing questionnaires via google form and distributing questionnaires to 230 students to schools. From the results of this data analysis, it shows that the ineffective quality of instruction, Appropriate levels of instruction, Incentive, and time felt by students. From the results of the analysis above, it can be concluded that this odd-even system can still be carried out if the pandemic continues, provided the teacher evaluates the obstacles faced by students during the odd-even system learning.